149k views
0 votes
Which expression is equivalent to (5x^3)(2x)^3

2 Answers

6 votes

For this case we have the following expression:


5x ^ 3 * (2x) ^ 3

Rewriting we have:


5x ^ 3 * (2x * 2x * 2x) =\\5x ^ 3 * 8x ^ 3 =

For properties of multiplication of power of the same base we have that:


a ^ m * a ^ n = a ^ {m + n}

So:


5x ^ 3 *8x ^ 3 = 40x ^ 6

Answer:


40x ^ 6

User John Rand
by
5.7k points
3 votes

Answer:


\large\boxed{(5x^3)(2x)^3=40x^6}

Explanation:


(5x^3)(2x)^3\qquad\text{use}\ (ab)^n=a^nb^n\\\\(5x^3)(2^3x^3)=(5x^3)(8x^3)\qquad\text{use commutative law}\\\\=(5\cdot8)(x^3x^3)\qquad\text{use}\ a^na^m=a^(n+m)\\\\=40x^(3+3)=40x^6

User Sayan
by
5.1k points